Challenge and Change
XIV, 287 p. 9 illus. in color.
Keywords: This edited volume addresses how the state system, the organizing political institution in world politics, copes with challenges of rapid change, unanticipated crises, and general turmoil in the twenty-first century. These disruptions are occurring against the background of declining US influence and the rising power of countries in Asia, Africa, and Latin America. Traditional inter-state security concerns coexist with new security preoccupations, such as rivalries likely to erupt over the resources of the global commons, the threat of cyber warfare, the ever-present threat of terrorism, and the economic and social repercussions of globalization. The contributors explore these key themes and the challenges posed by rapid change.